Determining Social Intelligence of Dental Students ar Various “Academic Levels by Trosmo Social Intelligence Scale” - Hina Ali, Muhammad Imtiaz, Khizer Mehmood, Salima Naveed Manji, Afshan Khanum (Pakistan Journal of Medical & Health Sciences, 2023)
Background/Introduction: Social intelligence is of great importance in the life of health care professionals because it is a significant factor of prediction and interpretation of human behavior in various contexts of social and clinical practice. The purpose of this study was to determine social intelligence of dental students at various academic levels by Trosmo Social Intelligence scale. Methods: This is a descriptive cross-sectional study conducted at various dental colleges of Pakistan. Re-validated Trosmo social intelligence questionnaires were distributed to undergraduate dental students to assess their social intelligence at various academic levels. Likert scale was used to assess the opinions and attitudes of the respondents. Results: The study consisted of 403 participants, of which 129 (32%) were male and 236 (58.6%) were female. The minimum age of the respondents was 18 and 28 being the maximum. The average values of social intelligence at various academic levels are as follows: 1.944 for BDS 1, 1.980 for BDS 2, 1.87 for BDS 3, 2.053 for BDS 4, respectively. Nor growth in all three component of social intelligence was identified. Conclusion: There is insignificant change in social intelligence of students at various academic levels and no significant link is found between the three dimensions of social intelligence and the upgrading academic levels, which is concerning. Keywords: Social intelligence; academic levels; TROSMO scale; dental students, social skills, clinical practice, healthcare, human behavior, professionalism, curriculum